Management of COMPlicAted intra‐abdominal collectionS after colorectal Surgery (COMPASS): protocol for a multicentre, observational, prospective international study of drain placement practices in colorectal surgery. (10th August 2020) - ,
Abstract: Aim: Postoperative drains have historically been used for the prevention and early detection of intra‐abdominal collections. However, current evidence suggests that prophylactic drain placement following colorectal surgery has no significant clinical benefit. This is reflected in the enhanced recovery after surgery (ERAS) guidelines, which recommend against their routine use. The Ileus Management International study found more than one‐third of participating centres across the world routinely used drains in the majority of colorectal resections. The aim of the present study is to audit international compliance with ERAS guidelines regarding the use of postoperative drains in colorectal surgery. Method: This prospective, multicentre audit will be conducted via the student‐ and trainee‐led EuroSurg Collaborative network across Europe, South Africa and Australasia. Data will be collected on consecutive patients undergoing elective and emergency colorectal surgery with 30‐day follow‐up. This will include any colorectal resection, formation of colostomy/ileostomy and reversal of stoma. The primary end‐point will be adherence to ERAS guidelines for intra‐abdominal drain placement. Secondary outcomes will include the following: time to diagnosis of intra‐abdominal postoperative collections; output and time to removal of drains; and 30‐day postoperative complications defined by the Clavien–Dindo classification. Conclusion: This protocol describes the methodology for the first international audit of intra‐abdominal drain placement after colorectal surgery. The study will be conducted across a large collaborative network with quality assurance and data validation strategies. This will provide a clear understanding of current practice and novel evidence regarding the efficacy and safety of intra‐abdominal drain placement in colorectal surgical patients.